Evaluación del grado de vulnerabilidad y adaptación frente al cambio climático de los sistemas agroforestales de café en fincas de la parroquia San Pedro de Vilcabamba provincia de Loja, - Guerrero Encalada, Gomer Guillermo (2024)
Climate change is affecting agriculture worldwide, and coffee production is no exception. Loja is the second-largest coffee-producing province in Ecuador, but its yields are low due to poor crop management and a lack of adaptation to climate change. This study evaluated the vulnerability and adaptation to climate change of coffee agroforestry systems in the San Pedro de Vilcabamba parish, a coffee-growing region where most people are farmers. The study used a qualitative approach, with surveys and field visits to assess the coffee plantations. The surveys evaluated exposure, impact, and adaptive capacity to climate change. Soil analysis and weather data from the past six years were also used to categorize vulnerability and adaptive capacity. The results showed a moderate level of vulnerability and adaptive capacity (3.23) in the 11 farms visited. The least common practices were fertilization, annual pruning, weeding, and thinning of shade trees. This shows that the 11 coffee farms in the agroforestry systems are vulnerable to climate change and have no adaptation system. There is no adequate management and control of the agroforestry systems.